The Influence of Learning Discipline and Time Management on Student Learning Achievement in Economics Subjects at MA Midanutta’lim Jogoroto - Zahrotul Ainiyah; Masruchan Masruchan (Darul Yasin Al Sys, 2026)
Learning achievement is a key indicator of educational success and is influenced by internal factors such as learning discipline and time management. In Islamic boarding school-based madrasahs, students must balance formal academic responsibilities with intensive religious activities, making discipline and effective time allocation essential for academic performance. This study aimed to analyze the influence of learning discipline and time management on students’ achievement in Economics subjects at MA Midanutta’lim Jogoroto during the 2025/2026 academic year. A quantitative survey design was employed, involving a population of 115 students and a sample of 90 students selected through proportional random sampling. Data were collected using questionnaires and academic records and were analyzed through multiple linear regression with SPSS version 27. The findings reveal that learning discipline had a positive and significant effect on learning achievement (Sig. = 0.000; β = 0.401), while time management also had a positive and significant effect (Sig. = 0.047; β = 0.240). Simultaneously, both variables significantly influenced learning achievement (F = 34.506; Sig. = 0.000) and explained 44.2% of the variance in students’ academic performance. The study concludes that stronger learning discipline and more effective time management contribute to improved Economics learning achievement. These findings contribute to educational management and learning behavior studies by highlighting the importance of self-regulated academic habits in Islamic boarding school-based madrasahs. Practically, the study implies that madrasahs should strengthen discipline development programs and provide time management training to support students’ academic success.